Improving The Capabilities Of Depohar 80 Maintenance Per-sonnel Through Education 4.0 In Order To Support The Du-ties Of The Indonesian Air Force - Darmawan, Ade H; Sadipung, Theresia Oktavia (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Increasing the capabilities of maintenance personnel at Depohar 80 TNI Air Force is very important to ensure operational readiness and aircraft reliability. Adoption of the Education 4.0 paradigm offers an effective solution in this effort. Education 4.0 emphasizes a learnercentered approach, utilizing advanced technology, and building a learning community, which provides an ideal framework for improving the competency of maintenance personnel at Depohar 80. The aim of this research is to explore how to improve the capabilities of Depohar 80 Maintenance Personnel through Education 4.0 in Order to Support the Duties of the Indonesian Air Force. The method used in this writing is a qualitative method. The results of this research show that the strategies implemented include developing a technology-based curriculum, providing adequate technological infrastructure, training trainers and facilitators, continuous evaluation and feedback, establishing learning communities, and utilizing online resources and networks. Each of these strategies is designed to overcome obstacles faced by personnel in improving their technical skills and competencies, in accordance with capability theory which emphasizes the importance of education, work skills, experience, motivation and work ethic. This approach allows maintenance personnel to access more interactive and in-depth training, gain skills relevant to the latest technology, and continuously improve their performance through constructive feedback. Implementation of Education 4.0 not only improves technical capabilities but also builds their capacity to learn and adapt independently, in accordance with the demands of the Industrial Revolution 4.0 era. The research conclusion is that through Education 4.0, Depohar 80 can achieve optimization of the capabilities of maintenance personnel, which in turn will support the TNI Air Force's duties more effectively and ensure the reliability and operational success of the aircraft.